PHARMACEUTICAL CARE IN COMMUNITY PHARMACIES DURING COVID-19 PANDEMIC: PHARMACISTS EXPERIENCE IN SERBIA - Stefanović, Nikola; Damnjanović, Ivana; Koraćević, Maja; Jovanović, Aleksandar; Catić-Đorđević, Aleksandra; Pavlović, Dragana; Veličković-Radovanović, Radmila (Acta medicae Medianae, 2024)
The importance of the pharmacist’s role in health care has become more pronounced during the COVID-19 pandemic as they were accessible and frontline healthcare professionals, who significantly contributed to ensuring uninterrupted access to essential healthcare services. This research aimed to examine the experiences of community pharmacists regarding the quality and extent of pharmaceutical care and patient counseling during the COVID-19 pandemic in relation to the pre-pandemic period. Also, this research aimed to investigate the informative role of community pharmacists considering the COVID-19 pandemic (possibility of infection, symptoms, protection, treatment, supplementation, etc.). In addition, the study examined whether the need for counseling and pharmacy services was greater during the period of high infection rates or not. A cross-sectional, quantitative study was conducted among community pharmacists, who accessed and filled out the online survey anonymously and voluntarily through a link on the Google platform. The obtained results showed that pharmacists who worked near COVID-19 clinics or hospitals more likely perceived that pharmaceutical care was significantly or completely compromised during the pandemic compared to other community pharmacists (38.78% vs. 21.88%, p = 0.005), while 40% of all respondents said that adequate information was provided to most patients compared to usual practice, including additional information they requested. Of all, 86% of pharmacists reported that many patients required additional information about COVID-19. The findings suggested that pharmacists who worked near COVID-19 clinics or hospitals perceived a lower increase in the requirement for counseling and pharmacy services during high infection rates periods compared to other pharmacists (53% vs. 69%, p < 0.001).